War 4.0 : Armed Conflict in an Age of Speed, Uncertainty and Transformation - Deane-Peter Baker; Mark Hilborne (ANU Press, 2025)
This volume explores the impact of technology and new domains on future warfare. It identifies several themes, and highlights the increasing complexity of the security environment and the uncertainty of future war. The sense of time and speed has been, and is being, compressed by developments in quantum technologies, the cyber domain, artificial intelligence, the increased capabilities of sensors and data collection, as well as new propulsion technologies such as hypersonic designs. Concepts regarding the shape and extent of the battlefield are challenged by the notion of hybrid war and sub-threshold tactics, as well as new domains in which competition is increasing, such as space. Further challenging the shape of the battlefield is the increased development of remote and autonomous warfare. Commercial developments will affect how military production is owned and managed, and how military forces are composed.Thus, a confluence of new technologies exists, combining to create the potential of fundamental transformation at many levels. This wave of technological change has been called the Fourth Industrial Revolution (4IR), characterised by an exponential rather than a linear rate of change, generated by convergence and complementarity of emerging technology domains. These may not affect the fundamental Clausewitzian nature of war, but they will likely affect its character. From a military perspective, the key will be the impact on the speed of operations and on the shape of the operational domain—the factors of time and space. The combination of these shifts will increasingly affect the perception of states and the degree of certainty in approaching and engaging in conflict.